Tapping into Florida's Craft Beer Market: A Brewer's Guide to Consumer Purchasing and Consumption Habits in the Sunshine State - Meri Hambaryan; Glory Orivri; Nathan Palardy; John Lai; Bachir Kassas (EDIS)
Florida’s craft beer industry has undergone explosive growth in the past decade, expanding sixfold from just 66 to 396 breweries, with an estimated economic impact of over $4 billion dollars in 2022. The craft beer sector is primarily small businesses that may lack large domestic breweries' resources and expertise to conduct in-house market research. Trade groups for craft breweries publish market research at the national level but do not often delve into state-specific nuances. This publication provides Florida breweries with data-driven marketing information on Florida beer consumers' purchase frequency, monthly beer expenditure, and preferred places to buy and drink beer. It includes a bulleted list of key consumer insights for craft breweries.